Enhancing Active, Innovative, Creative, Effective, and Enjoyable Learning in Information and Communication Technology Subjects - Engla Wita Rosmawaty Manalu (PT. Mifandi Mandiri Digital, 2024)
This study aims to enhance the quality of Active, Innovative, Creative, Effective, and Joyful Learning (commonly referred to as PAIKEM) in the Information and Communication Technology (ICT) subject at UPT SMP Negeri 15 Medan. The primary objective is to encourage active student participation, increase learning motivation, and foster a positive attitude toward ICT learning. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. Data were collected through observation, interviews, and learning outcome tests. The findings indicate that the implementation of PAIKEM strategies significantly improved student engagement, motivated students to participate more actively, and positively impacted their learning outcomes. Thus, the PAIKEM approach has proven to be effective in creating a more meaningful and enjoyable learning environment in ICT classes.